Authentic Female Leadership at Yasiska Vocational School: Its Influence on the Formation of a Transparent and Participatory School Culture - Delis Ahlia; Firda Zahraningtyas; Hasyim Asy’ari (al-Afkar, Journal For Islamic Studies, 2026)
The research aims to examine the influence of authentic female leadership on the formation of a transparent and participatory school culture at SMK Yasiska. Authentic female leadership is seen as a leadership model that focuses on integrity, openness, and authenticity in making decisions. A transparent and participatory school culture is believed to create an inclusive learning environment that supports student development. The method used in this research is a qualitative approach with in-depth interview techniques and observation of female principals and a number of teachers and students at SMK Yasiska. The results showed that authentic female leadership has an impact in creating a school culture that is open, communicative, and involves all parties in decision-making. In this case, the female principal at SMK Yasiska successfully applied leadership principles that prioritize honesty, justice, and empowerment, thus creating a more transparent and participatory school climate. This research contributes to enriching the understanding of the role of women's leadership in shaping a more democratic school culture.